The dynamics of household final consumption: The role of wealth channel - Esra Alp; Unal Seven (Central Bank Review (CBR), 2019)
Exploring dynamics of household final consumption is an important concern for policy-makers. Turkey had witnessed various financial shocks and crises over the last two decades. These turbulent economic periods affected consumption behaviour and therefore, other macroeconomic variables. In this paper, we examine the linkage between household final consumption and wealth in Turkey, arising from equity and housing market channels over the period from 1998 Q1 to 2016 Q2. We employ ARDL and FMOLS models in order to analyse long-term relationship and then, variance decomposition and impulse response analysis are used for verifying the effects of shocks. The results suggest that income, credit and housing wealth are positively, interest rate and equity market wealth are negatively associated with consumption. Variance decomposition and impulse response analyses imply that interest rate driven shocks may cause to a decline in asset prices and so aggregate consumption through consumption-wealth channel. These evidences may be beneficial for policymakers to understand the role of interest rate and asset prices on the consumption-wealth channel in Turkey.
Keywords: E21; E52; E58; 330; Consumption; Housing wealth; Financial wealth; Transmission channels; Variance decomposition; Impulse response